Evaluation of the Quality of Educational YouTube Videos on Endoscopic Choanal Atresia - Shirin Irani; Sevil Nasirmohtaram (Journal of Rhinology)
Background and Objectives YouTube has become a widely used educational platform for medical trainees in endoscopic surgery. However, the quality of surgical videos on this platform remains unregulated. This study evaluates the educational quality of YouTube videos on endoscopic choanal atresia repair using a validated assessment tool. Methods In this descriptive cross-sectional study, 50 YouTube videos on endoscopic choanal atresia surgery were analyzed. Video quality was assessed using the LAParoscopic surgery Video Educational GuidelineS (LAP-VEGaS) checklist, which evaluates content structure, procedural clarity, and outcomes reporting. Results Among 108 initially identified videos, 50 met the inclusion criteria. Video quality scores ranged from 1 to 16, with a median score of 7. The most frequently included elements were step-by-step approach (96%), patient anonymity (96%), and descriptive title (76%). Procedural clarity received moderate scores overall, with only the “step-by-step approach” achieving consistent quality. Outcomes reporting was notably deficient, with 90% of videos failing to address postoperative morbidity or complications. Conclusion Most YouTube videos on endoscopic choanal atresia surgery lack the quality required for effective surgical education. As digital platforms increasingly supplement traditional training, academic institutions and specialists should prioritize creating and sharing high-quality, standardized educational content on public platforms like YouTube.